Pengembangan Inovasi Kemasan Produk Untuk Meningkatkan Daya Tarik Umkm Wedang Jahe di Desa Sidodadi Asri - Rico Elhando Badri; Cahyani Pratisti; Anandha Sartika Putri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
This community service activity aims to solve the problems MSMEs face in home industrial products in Sidodadi Asri Village, Jati Agung District, South Lampung Province, by assisting MSMEs in developing product packaging designs. The rationale for the priority themes is to raise awareness of packaging through research on the importance of packaging, development of appropriate technology, and marketing networks to improve the competitiveness of processed products for the small business cottage industry. It was developed by optimizing potential through community empowerment that enhances the village of Sidodadi Asri. Envisioning how to implement problem-solving begins with coordination between the village chief and his MSME owner. The output that will be generated from community service activities is the right technology, in the form of packaging design and a high level of understanding of the importance of packaging through training in packaging development with shaping product brands and labels, creating innovative, engaging solutions and modern packaging. And also how to promote it through social media like Whatsapp and Instagram so that it is said to provide benefits for MSMEs to independently expand product distribution and independent use of e-commerce and social media as a means of promotion and sales marketing.